2013
DOI: 10.1161/circheartfailure.113.000187
|View full text |Cite
|
Sign up to set email alerts
|

Failing Heart of Patients With Type 2 Diabetes Mellitus Can Adapt to Extreme Short-term Increases in Circulating Lipids and Does Not Display Features of Acute Myocardial Lipotoxicity

Abstract: We hypothesized that (1) short-term extreme changes in FFA and triglyceride levels affect MyLC in patients with T2D and HF, and that (2) suppressed as opposed to increased circulating FFA and triglyceride increase myocardial contractility and cardiopulmonary exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The results from short-term studies have shown disappointing effects of increases in substrate accessibility on left ventricular function in patients with T2D and HF. 25 26 This indicates that possible beneficial effects of metabolic intervention may require long-term intervention. In the present randomized trial, patients with T2D and HF underwent 4 months of glycemic optimization.…”
Section: Discussionmentioning
confidence: 99%
“…The results from short-term studies have shown disappointing effects of increases in substrate accessibility on left ventricular function in patients with T2D and HF. 25 26 This indicates that possible beneficial effects of metabolic intervention may require long-term intervention. In the present randomized trial, patients with T2D and HF underwent 4 months of glycemic optimization.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the long standing type 2 diabetes [ 9 ], which increase the possibility of depressed sympathetic activity [ 23 ]. Nielsen et al [ 26 ] observed a tendency towards increased heart rate ( p = 0.08) due to high levels of lipid infusion versus low lipid infusion controls—this indicates that fast food may increase heart rate more than healthy foods.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography was performed using a GE VIVID 9E system (GE Medical System) with a 2.5‐MHz transducer and analyzed offline using EchoPAC version 113 (GE‐Vingmed Ultrasound), as described previously . Continuous‐wave Doppler imaging from multiple acoustic windows was used to explore the highest transaortic velocity and peak and mean gradients.…”
Section: Methodsmentioning
confidence: 99%